From a Helix to a Small Cycle: Metadynamics‐Inspired αvβ6 Integrin Selective Ligands. Issue 44 (2nd May 2018) - Di Leva, Francesco Saverio; Tomassi, Stefano; Di Maro, Salvatore; Reichart, Florian; Notni, Johannes; Dangi, Abha; Marelli, Udaya Kiran; Brancaccio, Diego; Merlino, Francesco; Wester, Hans‐Jürgen; Novellino, Ettore; Kessler, Horst; et al.
Abstract: The RGD‐recognizing αvβ6 integrin has only recently emerged as a major target for cancer diagnosis and therapy. Thus, the development of selective, low‐molecular‐weight ligands of this receptor is still in great demand. Here, a metadynamics‐driven design strategy allowed us to successfully convert a helical nonapeptide into a cyclic pentapeptide (6 ) showing remarkable potency and αvβ6 specificity. NMR and docking studies elucidated the reasons for the high affinity and selectivity of this compound, setting the ground for the rational design of new αvβ6‐specific small peptides or even peptidomimetics. In vivo PET imaging studies demonstrated the potential use of6 for medical applications. Abstract : A metadynamics‐driven drug design strategy was employed to transform a helical nonapeptide into a cyclic pentapeptide as a potent and selective ligand of the RGD‐recognizing αvβ6 integrin. This compound was further developed into a PET tracer for specific αvβ6‐mapping in vivo, prompting its use for cancer diagnosis and therapy.